The modified Bessel functions I3/4(x) and I−3/4(x) in certain fractional differential equations. Issue 1 (January 2021) - Funes, Jorge Olivares; Valero Kari, Elvis R.; Martin, Pablo
Abstract: Linear fracctional equations has been considered with modified Bessel functions I 3 / 4 ( x ) and I − 3 / 4 ( x ) as no-homogeneus part. The result have been found using Laplace transform. Dun results lead to generalized hypergeometric functions. Several Coincidences have found between the results for the modified Bessel functions of the some order by different sign. No limitations have been found for the fracctional derivative, with could be any real numbers. Some specific values of Alpha have been also consifered.